PERSEPSI GENERASI Z TERHADAP REVOLUSI SOSIAL PERANG CUMBOK DI KABUPATEN PIDIE - Fajri, Heri; Rahmadani, Sri Novi; Zaini, Muhammad (Jurnal Sosial Humaniora Sigli, 2023)
The armed conflict that occurred in Aceh from 1945 to 1946, which changed the social and cultural structure of the local community, is known as the Cumbok War. This research aims to (1) Find out Generation Z's understanding of the historical background and social context behind the Cumbok War. (2) Find out how social media information and technology influence Generation Z's perception of the historical events of the Cumbok War social revolution. The approach used in this research is a descriptive qualitative approach. This research was conducted in Cumbok Niwa village. Data collection methods were carried out using observation, interviews, literature, and documentation studies related to Generation Z's perceptions of the social revolution of the Cumbok War. The results of this research show that (1) Generation Z's understanding of the historical background and social context behind the Cumbuk War is still limited. The majority of Generation Z have minimal knowledge about the history of the conflict and a lack of awareness of the social factors that influenced the Cumbok War (2) Generation Z uses social media as the main source of information about the Social Revolutionary War in Cumbok. Digital technology influences the way Generation Z understands events. history of the social revolution of the Cumbok War. Keywords : Generation Z Perception, Social Revolution, Cumbok War